Detection of circulating tumor cells and their potential use as a biomarker for advanced renal cell carcinoma - Kim, Tae Heon; Kang, Yoon-Tae; Cho, Young-Ho; Kim, Jeong Hoon; Jeong, Byong Chang; Seo, Seong Il; Jeon, Seong Soo; Lee, Hyun Moo (Canadian Urological Association Journal, 2018)
Introduction: The aim of this study was to detect circulating tumor cells (CTCs) in patients with advanced renal cell carcinoma (RCC) using a novel CTC detection platform. Furthermore, we evaluated the clinical outcomes associated with a CTC-positive status. Methods: A total of 34 patients with advanced RCC (stage III or IV) were prospectively enrolled, and 104 peripheral blood samples were analyzed for the presence of CTCs at various time points. CTCs were isolated using a tapered-slit filter, which captures CTCs based on size and deformability. The presence of CTCs was confirmed using both staining and morphological criteria. CTC status was then correlated with clinical characteristics and survival outcomes. Results: CTCs were detected in 62% of patients during the pretreatment period, and the median CTC count was 2 (interquartile range 1–3). During the followup period, CTCs were detected in 56% (18/32), 65% (20/31), and 41% (7/17) of patients at one week, one month, and three months after treatment, respectively. Overall, CTCs were found in 57.9% (66/114) of blood samples in the range of 1–7 cells. Although no statistical significance was found, CTC detection in patients with stage IV disease was more common than in patients with stage III disease (68.4% vs. 53.3%). Two-year progression-free survival and cancer-specific survival tended to be lower in CTCpositive patients compared with CTC-negative patients. Conclusions: The tapered-slit filter is an efficient technique to detect CTCs in advanced RCC.